Preference, knowledge and utilization of midwives, childbirth education classes and doulas among U.S. black and white women: implications for pregnancy and childbirth outcomes. (26th November 2019) - Sperlich, Mickey; Gabriel, Cynthia; St. Vil, Noelle M.
ABSTRACT: This secondary analysis explored preference, knowledge and utilization of midwifery care, childbirth education and doula care among 627 black and white women at three Midwestern U.S. health clinics. Women who were white, more educated, not living in a high crime neighborhood, and privately insured were more likely to attend childbirth classes. Sociodemographic factors that predicted having heard about doula care included being more educated and having a partner. None of the sociodemographic variables predicted midwifery care. Education about existing childbearing resources and availability of low-cost options should be expanded, particularly for black women and those with low resources.